Concave shells of continuity modules - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 The inequality ω(t)≤_s>0(ω(s2)+ω(s)st) is proved, where ω(t) is a function of the modulus of continuity type and ω(t) is its smallest concave majorant. The consequences obtained for Jackson’s inequalities in C_2π are presented.